VGLUT2 Functions as a Differential Marker for Hippocampal Output Neurons - Wozny, Christian; Beed, Prateep; Nitzan, Noam; Pössnecker, Yona; Rost, Benjamin R.; Schmitz, Dietmar (Frontiers in Cellular Neuroscience, 2018)
The subiculum is the gatekeeper between the hippocampus and cortical areas. Yet, the lack of a pyramidal cell-specific marker gene has made the analysis of the subicular area very difficult. Here we report that the vesicular-glutamate transporter 2 (VGLUT2) functions as a specific marker gene for subicular burst-firing neurons, and demonstrate that VGLUT2-Cre mice allow for Channelrhodopsin-2 (ChR2)-assisted connectivity analysis.